The Correlation between Memorizing the Qur’an Ability and Students’ Logical-Mathematical Intelligence - Irsal, Irni Latifa; Yunita, Nurma (Universitas Islam Negeri Sunan Kudus, 2022)
A hypothesis telling that students' mathematics logical ability differences are caused by memorizing the Qur'an, is the focus of this research. The researcher in this research analyzes whether there is correlation between logical-mathematical ability and memorization the Qur'an and the overview. Quantitative and qualitative analysis is used to reveal the correlation between logical-mathematics intelligence and the Qur'an memorization. Logical-Mathematical Intelligence test, Qur'an memorization test, interview, and observation are used as instruments in the research. Twenty-eight students in the mathematics study program are as the subject of research where all students have already joined logical-mathematical subject. Based on the results obtained, overall, logical-mathematical intelligence and Qur'an memorization have a positive linear correlation. The more the students memorize the Qur’an the more the students have logical-mathematical intelligence. It is illustrated in the results, there are 6 different types of numerical indicators when viewed from the level of quantity and quality of memorizing the Qur'an. The same number is also reflected in abstract indicators and spatial relations. Each of them shows 6 different types of logical-mathematical intelligence when viewed from the level of quantity and quality of the Qur'an memorization. The research result also shows the benefits of memorizing the Qur'an which provides positive changes on students learning patterns. The development of the Qur'an memorization method is expected to be able to improve students' Qur'an memorization having an impact on students, intelligence especially logical-mathematical intelligence. Adanya dugaan bahwa perbedaan kemampuan logika matematika dimiliki mahasiswa disebabkan oleh hafalan Al-Qur’an, menjadi dasar dari penelitian ini. Penelitian ini menganalisi apakah ada hubungan antara logika matematika dan hafalan Al-Qur’an, serta gambaran dari hubungan tersebut. Analisis kuantitatif dan kualitatif digunakan untuk mengungkap hubungan antara logika matematika dan hafalan Al-Qur’an. Tes logika matematika, tes hafalan Al-Qur’an, wawancara, serta observasi digunakan sebagai instrument dalam penelitian. Dua puluh delapan mahasiswa tadris matematika menjadi subjek penelitian di mana seluruh mahasiswa telah mempelajari matakuliah logika matematika. Berdasarkan hasil yang didapat, secara keseluruhan, kecerdasan logika matematika dan hafalan Al-Qur’an memiliki hubungan linier positif. Semakin baik kuantitas dan kualitas hafalan Al-Qur’an yang dimiliki, maka akan semakin baik pula kemampuan logika matematika yang dimiliki mahasiswa. Tergambar pada hasil bahwa, terdapat 6 tipe perbedaan pada indikator numerikal jika dilihat dari tingkat kuantitias dan kualitas hafalan Al-Qur’an. Jumlah yang sama juga tergambar pada indikator abstrak dan relasi ruang. Masing-masing menunjukkan 6 tipe perbedaan kecerdasan logika matematika jika dilihat dari tingkat kuantitas dan kualitas hafalan Al-Qur’an. Hasil penelitian menunjukkan pula kebermanfaatan penghafalan Al-Qur'an yang memberikan perubahan positif dalam pola belajar mahasiswa. Pengembangan metode menghafal al-qur'an diharapkan mampu mengembangkan hafalan al-qur'an mahasiswa yang berdampak pula pada kecerdasannya